Peran Guru Dalam Menegakkan Tata Tertib Sekolah Di SDN 006 Bukit Kapur Kota Dumai - Doni Setiawan; Elpri Darta Putra (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
The role of the teacher in the school environment is not only as a teacher, there are so many teacher roles that the teacher must carry out. One of the teacher's roles in schools is to enforce school rules, where this order is very important to carry out so that discipline is embedded in students. In this study, the main objective is to describe how the role of teachers in enforcing school rules and regulations. Techniques for collecting the data needed in this study used interview, observation, and documentation techniques. To manage the data using an interactive analysis model from Miles and Huberman, namely collecting data, reducing data, presenting data, and drawing conclusions. In this study resulted in a style of role performed by the teacher such as using a role style that is seen in the process undertaken by the teacher in supervising students, making decisions, and enforcing rules and acting in determining a solution or problem that arises.